1998
DOI: 10.1046/j.1365-2443.1998.00222.x
|View full text |Cite
|
Sign up to set email alerts
|

A core region of the mafK gene IN promoter directs neurone‐specific transcription in vivo

Abstract: Background: MafK serves as a required subunit of erythroid transcription factor NF-E2 and also functions with various heterodimeric CNC family proteins. MafK expression begins in early mesoderm and is observed in mesenchymal and haematopoietic cells, as well as in neurones during mouse development. In mesodermal descendants, MafK mRNA begins with a distal first exon (called I M ), whereas the mRNA in neurones begins with a proximal first exon (I N ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…1C). This is consistent with the absence of tags corresponding to MafK in our SAGE analysis of long-term (9 d) NGF-treated cells (Table 1) and with the report by Motohashi et al (1998) Semiquantitative PCRs were performed with 25 cycles for MafK and 20 cycles for GAPDH. B, RT reactions were subjected to quantitative realtime PCR.…”
Section: Ngf Rapidly Elevates Mafk Expressionsupporting
confidence: 91%
“…1C). This is consistent with the absence of tags corresponding to MafK in our SAGE analysis of long-term (9 d) NGF-treated cells (Table 1) and with the report by Motohashi et al (1998) Semiquantitative PCRs were performed with 25 cycles for MafK and 20 cycles for GAPDH. B, RT reactions were subjected to quantitative realtime PCR.…”
Section: Ngf Rapidly Elevates Mafk Expressionsupporting
confidence: 91%
“…Taken together, it seems clear that all three small maf genes utilize multiple first exons. MafG does not appear to have tissue-specific first exons, such as the mafK I N exon that is employed exclusively in neurons (27). Nonetheless, expression analysis revealed that mafG first exons are utilized differentially in various tissues.…”
Section: Discussionmentioning
confidence: 95%
“…2) (Motohashi et al, 1996; Motohashi et al, 1998). In the 3’ region of MafK , there is an enhancer referred to as H ematopoietic and C ardiac E nhancer for Maf K (HCEK), which drives MafK expression in both hematopoietic and cardiac tissues (Katsuoka et al, 2000).…”
Section: Gene Structure and Expression Profile Of Smafsmentioning
confidence: 99%